IT PROFESSIONAL COMPETENCES AND THE REQUIREMENTS OF THE LABOUR MARKET: EXPERIENCE OF THE UNITED KINGDOM (Journal of Information Technologies in Education (ITE), 2009)
Understanding the employment market while defining specific skill sets associated with potential graduates is always important for courses in higher education.